Hubungan Parasosial dan Perilaku Loyalitas Fans dalam Fandom KPop di Indonesia - Pulung Setiosuci Perbawani; Almara Jati Nuralin (LONTAR: Jurnal Ilmu Komunikasi, 2021)
This paper investigates fandom as a phenomenon of communication science through an interdisciplinary perspective, especially in relation to the psychology discipline of communication and consumer behavior. The researcher seeks to investigate the correlation between parasocial relationships (Parasocial relationships/PSR) and fan loyalty behavior, specifically the consumption behavior of the brands and products associated with their idols. The research will be carried out using survey methods, with PSI Process Scale to measure parasocial relationship variables, and commitment models to measure fan loyalty behavior. From the questionnaires distributed online, 271 valid questionnaires were obtained which were analyzed using mean analysis, correlation test, and cross tabulation analysis. The results showed that there was a significant relationship between parasocial relationships and fan loyalty. The results also show that the closest relationship is shown by the behavioral dimension with the interaction dimension, while the relationship with the lowest score is shown by the relationship between the perceptual-cognitive dimension and desire to acquire.